2014
DOI: 10.1111/petr.12388
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk factors and cardiac disorders in long‐term survivors of pediatric liver transplantation

Abstract: The MetS and cardiovascular disease are leading causes of late morbidity in adult liver transplantation recipients; however, limited data are available in pediatric liver transplantation. A single-center retrospective review was undertaken for patients who had a liver transplantation before 18 yr of age and were >5 yr post-transplantation, to study the prevalence of MetS, its components, and cardiac disorders. Fifty-eight patients were included in the study with a mean age at transplantation of 6.3 ± 6.1 yr an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 46 publications
2
11
1
Order By: Relevance
“…(29) The high prevalence of low HDL seen in our cohort has been observed in other cohorts of pediatric LT recipients; (3, 9) this will be an important topic for future study, as low HDL in children is associated with poor VLDL and triglyceride clearance. The apparent protective effect of LT against other dyslipidemias has been reported in pediatric cohorts (3, 18) but not in adults.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…(29) The high prevalence of low HDL seen in our cohort has been observed in other cohorts of pediatric LT recipients; (3, 9) this will be an important topic for future study, as low HDL in children is associated with poor VLDL and triglyceride clearance. The apparent protective effect of LT against other dyslipidemias has been reported in pediatric cohorts (3, 18) but not in adults.…”
Section: Discussionsupporting
confidence: 52%
“…(3,9,10) However, these reports are largely based on data collected sporadically during clinical care rather than systematically for research purposes and have not included matched control groups. Furthermore, pediatric LT recipients do not typically undergo rigorous evaluation for pre-diabetes, an important component of metabolic syndrome tied to long-term morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…We found left ventricular hypertrophy in 11% of our patients. Published reports on left ventricular hypertrophy in children who have undergone LT describe variable frequencies, ranging from 0% to 43% . Small sample sizes and a huge variability in follow‐up time after transplantation render a direct comparison of these studies difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Asymptomatic interventricular septal hypertrophy and early diastolic dysfunction have been described, (21) whereas other studies did not find any differences in echocardiographic parameters between children after LT and healthy controls. (22) Baskar et al demonstrated left ventricular hypertrophy in 10 out of 23 patients >5 years after LT. (23) No large-scale prospective studies that correlate cardiac function and morphometry with other CV RFs have been published in the context of pediatric LT to date.…”
Section: Original Article | 753mentioning
confidence: 99%
“…We have recently shown that pediatric liver transplant recipients have a higher risk of pre‐hypertension and hypertension, impaired glucose tolerance (pre‐diabetes), and low HDL than matched peers, even after controlling for obesity and corticosteroid use . In long‐term follow‐up of these children, the prevalence of PTMS, indicating 3 or more of the diagnostic features, is estimated to be 14%‐20% . These conditions are identifiable in the pre‐clinical stage, and early identification with active management may prevent long‐term consequences.…”
Section: Introductionmentioning
confidence: 99%